On a method combining the data language and the programming language - Tang, Nguyen Van (Journal of Computer Science and Cybernetics, 2015)
A programming language and the database language will be combined one to another in such a way, that an application source program, which a mixture of statements of the host and database languages  instead, can be now separated into two source modules, the one on the host language and the other on the data base. By the host standard compiled into object modules. The LINKEP EDITOR of the operating system links those modules into a load module that corresponds to the original mixed program.